Porous carbon structure, method for manufacturing the same, and lithium secondary battery containing the same

By using porous carbon precursors with core-shell structure as sulfur carriers for the positive electrode active material in lithium-sulfur secondary batteries, the problem of poor circulation characteristics of lithium-sulfur secondary batteries is solved, and higher circulation stability is achieved and Electrochemical properties.

CN116261563BActive Publication Date: 2025-02-14LG ENERGY SOLUTION LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280006578.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-01-26
Filing Date
2022-01-27
Publication Date
2025-02-14
Estimated Expiration
2042-01-27

AI Technical Summary

Technical Problem

Lithium-sulfur secondary batteries have poor circulation characteristics in commercial use, and existing methods have shortcomings in achieving commercialization, and a new method is needed to improve circulation characteristics.

Method used

Using a porous carbon precursor with a core-shell structure as the sulfur support of the positive electrode active material, a porous carbon precursor with a high specific surface area and large porosity is formed by doping N and S heterogeneous elements on the surface of the MOF to improve conductivity and inhibits the dissolution of polysulfides.

Benefits of technology

By using porous carbon precursors with core-shell structures, the cycle stability and electrochemical performance of lithium-sulfur secondary batteries can be effectively improved and the service life of the battery can be extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116261563B_ABST
    Figure CN116261563B_ABST
Patent Text Reader

Abstract

The present invention relates to a porous carbon precursor and a method for preparing the same. More particularly, the porous carbon precursor comprises a MOF having a core-shell structure, and because the constituent elements of the pore structures of a first MOF contained in the core and a second MOF contained in the shell are different, when used as a sulfur carrier for a lithium secondary battery containing sulfur as a positive electrode active material, polysulfides generated at the positive electrode are prevented from being dissolved into an electrolyte, thereby improving the performance and life characteristics of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application claims the benefit of priority based on Korean Patent Application No. 2021-0011621 filed on January 27, 2021 and Korean Patent Application No. 2022-0011827 filed on January 26, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a porous carbon precursor that can be used as a positive electrode material for a lithium secondary battery, a preparation method thereof, and a lithium secondary battery comprising the same. Background Art

[0003] Lithium-sulfur (Li-S) secondary batteries as energy storage devices have a theoretical energy density of 2600Wh / kg and a theoretical capacity of 1672mAh / g, and are gaining attention as next-generation energy storage devices because they exhibit an energy density 3 to 5 times that of conventional lithium batteries. However, lithium-sulfur secondary batteries have poor cycle characteristics in commercial use, and thus research has been conducted to improve cycle characteristics using a variety of methods.

[0004] In particular, by using graphene and activated carbon, which are carbon-based materials, as templates, methods of preventing sulfur from expanding in volume and improving conductivity at the same time are mainly used. However, these methods also have many shortcomings in achieving commercialization, and thus the situation is that another method must be proposed for commercialization.

[0005] A metal organic framework (MOF) is synthesized by hydrothermal synthesis of metal precursors and organic ligands (organic linkers) in a specific solvent, and is a three-dimensional porous material having a repeating array of metal blocks and organic ligands to be fabricated.

[0006] MOF has micropores and mesopores of various sizes and has been used as a gas storage medium due to its very wide specific surface area. In addition, MOF has not been used in electrochemistry due to the problem of poor conductivity, but recently, nano-sized MOFs have been synthesized and used for electrochemical purposes, thereby increasing the use of metal organic frameworks.

[0007] Furthermore, MOF can have various combinations of metal precursors and organic ligands, so that it can realize thousands of crystal structures, and can contain various functional groups, thereby being very useful in terms of use.

[0008] This MOF can be prepared into a porous carbon precursor with high specific surface area and large porosity through a carbonization process via heat treatment.

[0009] However, even porous carbon precursors with high specific surface area and large porosity have limitations in improving energy efficiency when applied to energy devices. Therefore, it is necessary to develop a porous carbon precursor that can improve energy efficiency by improving the reactivity of energy devices.

[0010] [Prior art literature]

[0011] [Patent Document]

[0012] (Patent Document 1) Korean Patent Publication No. 2020-0021214

[0013] (Patent Document 2) Korean Patent Publication No. 2012-0063925 Summary of the invention

[0014] [Technical issues]

[0015] Therefore, the present invention aims to provide a porous carbon precursor which is a carrier for sulfur contained in a positive electrode active material for a lithium-sulfur secondary battery, the porous carbon precursor being able to compensate for the insulating property of sulfur, thereby improving conductivity and inhibiting dissolution of polysulfide from the positive electrode.

[0016] Therefore, an object of the present invention is to provide a porous carbon precursor comprising MOF having a core-shell structure and a preparation method thereof.

[0017] In addition, another object of the present invention is to provide a lithium secondary battery comprising the porous carbon precursor.

[0018] [Technical solution]

[0019] In order to achieve the above object, the present invention provides a porous carbon precursor having a core-shell structure, wherein the core comprises a first MOF (metal organic framework) and the shell comprises a second MOF, wherein the second MOF is doped with a heteroelement including at least one of N and S.

[0020] The present invention also provides a method for preparing a porous carbon precursor, the method comprising the following steps: (S1) heating a mixed solution obtained by dissolving a metal precursor and a first organic ligand precursor in an organic solvent to form a MOF; (S2) adding a second organic ligand containing at least one of N and S to the mixed solution and heating to form a MOF having a core-shell structure; and (S3) carbonizing the MOF having a core-shell structure formed in step (S2).

[0021] [Beneficial Effects]

[0022] The porous carbon precursor according to the present invention has a core-shell structure in which the core and the shell respectively contain MOFs having different pore structures, and therefore when used as a sulfur carrier for a positive electrode for a lithium-sulfur secondary battery, it is possible to physically prevent polysulfide generated from the positive electrode from eluting into the electrolyte.

[0023] In addition, in the porous carbon precursor having a core-shell structure, since the shell contains a heteroelement such as N or S, when used as a sulfur carrier for a positive electrode for a lithium-sulfur secondary battery, polysulfides generated in the positive electrode are well physically or chemically adsorbed due to the heteroelement, thereby preventing the polysulfides from being eluted into the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a schematic diagram illustrating a process of forming a MOF having a core-shell structure in a method of preparing a MOF according to the present invention.

[0025] Figure 2 are scanning electron microscope (SEM) images of the MOFs prepared in Examples 1 and 2 and Comparative Example 1, respectively.

[0026] Figure 3 : are graphs (2θ level) showing the results of XRD (X-ray diffraction) analysis of the porous carbon precursors prepared in Example 1 and Comparative Examples 1, 2 and 3, respectively.

[0027] Figure 4 are optical microscope photographs of the porous carbon precursors prepared in Examples 1 and 2 and Comparative Examples 1, 2 and 3, respectively.

[0028] Figure 5 The graphs show the results of Fourier transform infrared spectroscopy (FT-IR) analysis of MOF and its raw materials prepared in Example 1 and Comparative Example 1, respectively.

[0029] Figure 6 The results of focused ion beam energy dispersive X-ray spectroscopy (FIB-EDS) measurement of the MOF prepared in Example 1 are shown.

[0030] Figure 7 The results of scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) measurement of the porous carbon precursor prepared in Example 2 are shown.

[0031] Figure 8a and Figure 8b The results of X-ray photoelectron spectroscopy (XPS) measurements of the porous carbon precursors prepared in Example 1 and Example 2 are shown respectively.

[0032] Figures 9a to 9c Graphs showing the BET analysis results of the porous carbon precursors prepared in Examples and Comparative Examples, respectively.

[0033] Fig.10 Graphs showing electrochemical performance of a lithium-sulfur secondary battery depending on the porous carbon precursor material contained in the positive electrode.

[0034] Fig.11a and Fig.11b Graphs showing the capacities of batteries including Example 1 and Comparative Example 1 after 1 cycle and 30 cycles.

[0035] Fig.12a is a graph showing changes in the NMR peak of the porous carbon precursor of Example 1 according to the synthesis time, and Figure 12b It is a graph showing changes in NMR peaks of Example 1 and Comparative Examples 1, 2, and 3.

[0036] Fig.13 : are photographs showing the measurement results of the contact angles of the electrodes including the porous carbon precursors of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0037] Hereinafter, the present invention will be described in more detail to help understanding of the present invention.

[0038] The terms and words used in this specification and claims should not be construed as limited to common or dictionary terms, and should be construed as meanings and concepts consistent with the technical idea of ​​the present invention on the basis of the principle that the inventor can appropriately define the concepts of the terms to describe his invention in the best possible manner.

[0039] As used herein, the term "layered structure" refers to a structure in which a shell is formed on a core in the porous carbon precursor having a core-shell structure in the form of a separate layer. In this case, the shell may be formed entirely or partially on the core.

[0040] Porous carbon precursor

[0041] The present invention relates to a porous carbon precursor having a core-shell structure, wherein the core may include a first metal organic framework (MOF), and the shell may include a second MOF, and wherein the second MOF may be doped with a heteroelement including at least one of N and S.

[0042] The first MOF and the second MOF have different pore structures and elemental compositions, and the second MOF forms a layer on the entire surface or a portion of the surface of the first MOF, thereby forming a porous carbon precursor having a core-shell structure. In this case, the pore structure may refer to the pore volume and the size of the pores.

[0043] Specifically, the shell is different from the core in that the shell is doped with heteroatoms and develops micropores (micropores account for the majority). Through this structure, the dissolution of LiPS can be suppressed chemically (heteroatom doping) and physically (micropores) during the operation of lithium secondary batteries such as lithium-sulfur secondary batteries.

[0044] For example, the specific surface area of ​​the first MOF may be 1700 to 2000 m 2 / g and the pore volume may be 1.9 to 2.5 cc / g, and the specific surface area of ​​the second MOF may be 900 to 1300 m 2 / g and the pore volume can be from 0.8 to 1.0 cc / g.

[0045] In the present invention, the porous carbon precursor may have different pore volumes and specific surface areas depending on the type of heteroelement doped into the second MOF of the shell. For example, if the heteroelement is N, micropores are developed in the porous carbon precursor, thereby increasing the specific surface area, and the pore volume may decrease. On the other hand, if the heteroelement is S, mesopores and micropores are developed in the porous carbon precursor, thereby increasing both the specific surface area and the pore volume. There is no particular limitation on the diameters of the micropores and mesopores, but the diameter of the micropores may be greater than 1 nm and less than 5 nm, and the diameter of the mesopores may be 5 nm to 10 nm.

[0046] In the present invention, there is no particular restriction on the pore volume of the porous carbon precursor, but as the pore volume increases, it can be suitable as a positive electrode material for a lithium secondary battery. For example, when the porous carbon precursor is used as a positive electrode material for a lithium secondary battery, as the pore volume of the porous carbon precursor increases, the sulfur (S8) contained in the positive electrode active material can be more impregnated and the structure of the positive electrode tank can be prevented from being damaged by the volume expansion that occurs during the mutual conversion of sulfur (S8) and lithium polysulfide (LiPS).

[0047] Therefore, when the porous carbon precursor is applied to a positive electrode material for a lithium secondary battery to be used as a sulfur carrier, the pore volume of the porous carbon precursor can be 1.5cc / g to 4.5cc / g, specifically 1.5cc / g or more, 2.0cc / g or more, or 2.5cc / g or more and 3.5cc / g or less, 4.0cc / g or less, or 4.5cc / g or less.

[0048] The pore volume of the porous carbon precursor may also vary depending on the type of heteroelement. For example, if the heteroelement included in the porous carbon precursor is N, the porous carbon precursor may include micropores.

[0049] In the present invention, the specific surface area of ​​the porous carbon precursor is not particularly limited, but as the specific surface area increases, sites for redox reactions between Li ions and sulfur can be sufficiently provided, allowing electrochemical reactions to proceed smoothly during charge and discharge of the lithium secondary battery.

[0050] Therefore, the specific surface area of ​​the porous carbon precursor can be 1500 to 3000 m 2 / g, specifically 1500m 2 / g or above or 1800m 2 / g and above and 2500m 2 / g or below 3000m 2 / g or less. If the specific surface area of ​​the porous carbon precursor is less than 1500m 2 / g, the active material cannot be fully loaded. If the specific surface area of ​​the porous carbon precursor exceeds 3000m 2 / g, more process time and cost than necessary may be incurred to achieve the specific surface area.

[0051] In the present invention, the porous carbon precursor may contain metal ions and organic ligands as components constituting the frameworks of the first MOF and the second MOF.

[0052] The metal ion may be one or more ions of metals selected from Groups 1 to 16 of the periodic table. Specifically, the metal ion may be at least one selected from the following: Li + 、Na + , K + , Rb + 、Be 2+ Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ Sc 3 + , Y 3+ 、Ti 4+ 、Zr 4+ , Hf + 、V 4+ 、V 3+ 、V 2+ , Nb 3+ 、 3+ Cr 3+ 、Mo 3+ , W 3+ , Mn 3+ , Mn 2+ 、Re 3+ 、Re 2+ , Fe 3+ , Fe 2+ 、Ru 3 + 、Ru 2+ , Os 3+ , Os 2+ 、Co 3+ 、Co 2+ , Rh2+ , Rh + , Ir 2+ , Ir + 、Ni 2+ 、Ni + , Pd 2+ , Pd + , Pt 2+ , Pt + , Cu 2+ , Cu + 、Ag + 、Au + 、Zn 2+ 、Cd 2+ , Hg 2+ 、Al 3+ , Ga 3+ 、In 3+ , Tl 3+ 、Si 4+ 、Si 2+ ,Ge 4+ ,Ge 2+ Sn 4+ Sn 2+ , Pb 4+ , Pb 2+ 、As 5+ 、As 3+ 、As + , Sb 5+ , Sb 3+ , Sb + 、Bi 5+ 、Bi 3+ and Bi + .

[0053] The organic ligand may be at least one selected from the following: halides (fluorine, chlorine, bromine, iodine), carboxylates, cyano groups, isocyanate groups, isothiocyanate groups, nitrile groups, pyridyl groups, nitroso groups, nitro groups, and phosphate groups. As a specific example, the organic ligand may be 4,4-bipyridine, benzene-1,4-dicarboxylate, or a derivative thereof.

[0054] In addition, the molar ratio of metal ions to organic ligands contained in MOF may be 1:0.2 to 5, preferably 1:0.3 to 4.5, and more preferably 1:0.5 to 4. If the molar ratio of organic ligands to metal ions is lower than the above range, the porosity may be reduced. If the molar ratio of organic ligands to metal ions exceeds the above range, the size of the pores may be reduced.

[0055] Method for preparing porous carbon precursor

[0056] The present invention also provides a method for preparing a porous carbon precursor, the method comprising the following steps: (S1) heating a mixed solution obtained by dissolving a metal precursor and a first organic ligand precursor in an organic solvent to form a MOF; (S2) adding a second organic ligand containing at least one of N and S to the mixed solution and heating to form a MOF having a core-shell structure; and (S3) carbonizing the MOF having a core-shell structure formed in step (S2).

[0057] Hereinafter, the method for preparing a porous carbon precursor according to the present invention will be described in more detail with respect to each step.

[0058] In the present invention, in step (S1), MOF can be formed by heating a mixed solution obtained by dissolving a metal precursor and a first organic ligand precursor in an organic solvent.

[0059] The reaction conditions for forming the MOF are heating at a temperature of 100 to 150°C for 6 to 40 hours.

[0060] If the reaction temperature is lower than 100° C., it is difficult to initiate a crystal formation reaction, and thus MOF may not be formed. If the reaction temperature exceeds 150° C., MOF may not be formed.

[0061] In addition, if the reaction time is less than 6 hours, the reaction is terminated in a state where an intermediate product is formed, or the reaction is terminated in a mixed state of MOF and the intermediate product. If the reaction time exceeds 40 hours, the time required for the process may be too long, thereby reducing the process efficiency.

[0062] The metal precursor may be a compound containing the above-mentioned metal ions. For example, the metal precursor may include a zinc precursor, and the zinc precursor may include at least one selected from the following: zinc nitrate hexahydrate (Zn(NO3)2·6H2O), zinc acetate dihydrate (Zn(CH3CO2)2·2H2O) and zinc sulfate hexahydrate (ZnSO4·6H2O).

[0063] In addition, the first organic ligand precursor may include at least one selected from the following: benzene-1,4-dicarboxylic acid, benzene-1,3,5-tricarboxylic acid, 2-methylimidazole, oxalic acid, malonic acid, succinic acid, glutaric acid, phthalic acid, isophthalic acid, terephthalic acid, 2-hydroxy-1,2,3-propanetricarboxylic acid, 1H-1,2,3-triazole, 1H-1,2,4-triazole and 3,4-dihydroxy-3-cyclobutene-1,2-dione, preferably 1,4-benzenedicarboxylic acid.

[0064] In addition, the organic solvent may include at least one selected from the following: dimethyl carbonate, dimethylformamide (DMF), N-methylformamide, sulfolane (tetrahydrothiophene-1,1-dioxide), 3-methylsulfolane, N-butyl sulfone, dimethyl sulfoxide, pyrrolidone (HEP), dimethyl piperidone (DMPD), N-methylpyrrolidone (NMP), N-methylacetamide, dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), diethylacetamide (DEAc), dipropylacetamide (DPAc), ethanol, propanol, butanol, hexanol, ethylene glycol, tetrachloroethylene, propylene glycol, toluene, tripentine, methyl acetate, ethyl acetate, petroleum ether, acetone, cresol and glycerol, preferably dimethylformamide (DMF).

[0065] In the present invention, in step (S2), a second organic ligand precursor containing at least one of N and S may be added to the mixed solution formed with MOF and heated to form a MOF having a core-shell structure. In this case, the second organic ligand may be used in the state of a solution dissolved in an organic solvent. The organic solvent may be the same as or different from the range of the type of the organic solvent used in step (S1).

[0066] The reaction conditions for synthesizing MOF having a core-shell structure are heating at 35° C. to 100° C. for 15 minutes to 25 hours. If the reaction temperature or time is less than such reaction temperature or time, the ligand exchange reaction rate is too slow. If the reaction temperature or time exceeds such reaction temperature or time, the crystallinity may be destroyed by heat.

[0067] The synthesized MOF can be supported in a second organic ligand precursor solution so as to be able to react. In this case, the synthesized MOF can be supported in a second organic ligand solution in a crystalline state after washing, activation and drying. In the second organic ligand precursor solution supporting the MOF, a solvent-assisted ligand exchange reaction occurs, so that the surface of the MOF is doped with at least one of N and S, which are heteroelements and are contained in the second organic ligand precursor.

[0068] In this case, the MOF interior not doped with heteroelement in the MOF can be referred to as the first MOF, and the surface portion doped with heteroelement can be classified as the second MOF. In addition, the first MOF is referred to as the core, and the second MOF is referred to as the shell, thereby being able to form a MOF having a core-shell structure.

[0069] Generally, a solvent-assisted ligand exchange reaction is a reaction in which a ligand solution exchanges the parent ligand and daughter ligand of a parent MOF and obtains a daughter MOF that retains the topological structure of the parent MOF. At this time, all parent MOFs are converted into daughter MOFs according to the control of reaction conditions (e.g., temperature, concentration, crystal size, etc.) and the characteristics of the daughter ligands, or they are sequentially converted from the surface of the parent MOF to form a core-shell structure. During the ligand exchange process, the ΔG associated with the linker exchange process converges to zero (0), which can be considered as equilibrium.

[0070] According to one embodiment of the present invention, the parent ligand is terephthalic acid and the daughter ligand is 2-aminoterephthalic acid, and during the exchange process, the parent MOF is not completely converted into the daughter MOF due to the steric hindrance of the amine group present in the 2-aminoterephthalic acid, thereby forming a core-shell structure.

[0071] Ligand exchange can be confirmed by a change in crystal color, a yellow boundary on OM, FT-IR, FIB-EDS, NMR, etc., and the conversion rate can be determined by NMR analysis.

[0072] Figure 1 is a schematic diagram illustrating a process of forming a MOF having a core-shell structure in a method of preparing a MOF according to the present invention.

[0073] refer to Figure 1 , ① shows a schematic diagram of the MOF formed in step (S1). ② shows a schematic diagram of the initial MOF, wherein the surface of the MOF begins to be doped with N while the solvent-assisted ligand exchange reaction between the MOF and the second organic ligand precursor is started in step (S2). ③ is a schematic diagram of a core-shell structured MOF divided into a first MOF and a second MOF, wherein the solvent-assisted ligand exchange reaction is completed and the surface of the MOF is doped with heteroelements. At this time, the second MOF forming the shell is doped with heteroelements.

[0074] The second organic ligand precursor may contain one or more of N and S.

[0075] The second organic ligand precursor containing N may include at least one selected from the following: 2-aminoterephthalic acid, 4-aminophthalic acid, 4-aminoisophthalic acid, 5-aminoisophthalic acid, 2,5-diaminoterephthalic acid, 2,2'-diamino-4,4'-stilbene dicarboxylic acid, 5-cyano-1,3-benzenedicarboxylic acid, 2-methylimidazole and 4,4',4"-s-triazine-2,4,6-triyl-tribenzoic acid. Hereinafter, the present invention will be described in more detail to help understand the present invention.

[0076] The terms and words used in this specification and claims should not be construed as limited to common or dictionary terms, and should be construed as meanings and concepts consistent with the technical idea of ​​the present invention on the basis of the principle that the inventor can appropriately define the concepts of the terms to describe his invention in the best possible manner.

[0077] As used herein, the term "layered structure" refers to a structure in which a shell is formed on a core in the porous carbon precursor having a core-shell structure in the form of a separate layer. In this case, the shell may be formed entirely or partially on the core.

[0078] Porous carbon precursor

[0079] The present invention relates to a porous carbon precursor having a core-shell structure, wherein the core may include a first metal organic framework (MOF), and the shell may include a second MOF, and wherein the second MOF may be doped with a heteroelement including at least one of N and S.

[0080] The first MOF and the second MOF have different pore structures and elemental compositions, and the second MOF forms a layer on the entire surface or a portion of the surface of the first MOF, thereby forming a porous carbon precursor having a core-shell structure. In this case, the pore structure may refer to the pore volume and the size of the pores.

[0081] Specifically, the shell is different from the core in that the shell is doped with heteroatoms and develops micropores (micropores account for the majority). Through this structure, the dissolution of LiPS can be suppressed chemically (heteroatom doping) and physically (micropores) during the operation of lithium secondary batteries such as lithium-sulfur secondary batteries.

[0082] For example, the specific surface area of ​​the first MOF may be 1700 to 2000 m 2 / g and the pore volume may be 1.9 to 2.5 cc / g, and the specific surface area of ​​the second MOF may be 900 to 1300 m 2 / g and the pore volume can be from 0.8 to 1.0 cc / g.

[0083] In the present invention, the porous carbon precursor may have different pore volumes and specific surface areas depending on the type of heteroelement doped into the second MOF of the shell. For example, if the heteroelement is N, micropores are developed in the porous carbon precursor, thereby increasing the specific surface area, and the pore volume may decrease. On the other hand, if the heteroelement is S, mesopores and micropores are developed in the porous carbon precursor, thereby increasing both the specific surface area and the pore volume. There is no particular limitation on the diameters of the micropores and mesopores, but the diameter of the micropores may be greater than 1 nm and less than 5 nm, and the diameter of the mesopores may be 5 nm to 10 nm.

[0084] In the present invention, there is no particular restriction on the pore volume of the porous carbon precursor, but as the pore volume increases, it can be suitable as a positive electrode material for a lithium secondary battery. For example, when the porous carbon precursor is used as a positive electrode material for a lithium secondary battery, as the pore volume of the porous carbon precursor increases, the sulfur (S8) contained in the positive electrode active material can be more impregnated and the structure of the positive electrode tank can be prevented from being damaged by the volume expansion that occurs during the mutual conversion of sulfur (S8) and lithium polysulfide (LiPS).

[0085] Therefore, when the porous carbon precursor is applied to a positive electrode material for a lithium secondary battery to be used as a sulfur carrier, the pore volume of the porous carbon precursor can be 1.5cc / g to 4.5cc / g, specifically 1.5cc / g or more, 2.0cc / g or more, or 2.5cc / g or more and 3.5cc / g or less, 4.0cc / g or less, or 4.5cc / g or less.

[0086] The pore volume of the porous carbon precursor may also vary depending on the type of heteroelement. For example, if the heteroelement included in the porous carbon precursor is N, the porous carbon precursor may include micropores.

[0087] In the present invention, the specific surface area of ​​the porous carbon precursor is not particularly limited, but as the specific surface area increases, sites for redox reactions between Li ions and sulfur can be sufficiently provided, allowing electrochemical reactions to proceed smoothly during charge and discharge of the lithium secondary battery.

[0088] Therefore, the specific surface area of ​​the porous carbon precursor can be 1500 to 3000 m 2 / g, specifically 1500m 2 / g or above or 1800m 2 / g and above and 2500m 2 / g or below 3000m 2 / g or less. If the specific surface area of ​​the porous carbon precursor is less than 1500m 2 / g, the active material cannot be fully loaded. If the specific surface area of ​​the porous carbon precursor exceeds 3000m 2 / g, more process time and cost than necessary may be incurred to achieve the specific surface area.

[0089] In the present invention, the porous carbon precursor may contain metal ions and organic ligands as components constituting the frameworks of the first MOF and the second MOF.

[0090] The metal ion may be one or more ions of metals selected from Groups 1 to 16 of the periodic table. Specifically, the metal ion may be at least one selected from the following: Li + 、Na + , K + , Rb + 、Be2+ 、Mg 2+ 、Ca 2+ 、Mr 2+ 、Ba 2+ 、Sc 3 + 、Y 3+ 、Tea 4+ 、Zr 4+ 、Hf + 、V 4+ 、V 3+ 、V 2+ 、Nb 3+ 、Ta 3+ 、Cr 3+ 、Mo 3+ 、W 3+ 、 Mr 3+ 、 Mr 2+ 、Re 3+ 、Re 2+ 、Fe 3+ 、Fe 2+ 、Ru 3 + 、Ru 2+ 、Os 3+ 、Os 2+ 、Co 3+ 、Co 2+ 、Rh 2+ 、Rh + 、Ir 2+ 、Ir + 、No 2+ 、No + 、Pd 2+ 、Pd + 、Pt 2+ 、Pt + 、 Cu 2+ 、 Cu + 、Ag + 、I + 、Zn 2+ 、Cd 2+ 、Hg 2+ 、Al 3+ 、Ga 3+ 、In 3+ 、Tl 3+ 、Si 4+ 、Si 2+ 、Ge 4+ 、Ge 2+ 、Sn 4+ 、Sn 2+ 、Pb 4+ 、Pb 2+ 、As 5+ 、As 3+ 、As+ , Sb 5+ , Sb 3+ , Sb + 、Bi 5+ 、Bi 3+ and Bi + .

[0091] The organic ligand may be at least one selected from the following: halides (fluorine, chlorine, bromine, iodine), carboxylates, cyano groups, isocyanate groups, isothiocyanate groups, nitrile groups, pyridyl groups, nitroso groups, nitro groups, and phosphate groups. As a specific example, the organic ligand may be 4,4-bipyridine, benzene-1,4-dicarboxylate, or a derivative thereof.

[0092] In addition, the molar ratio of metal ions to organic ligands contained in MOF may be 1:0.2 to 5, preferably 1:0.3 to 4.5, and more preferably 1:0.5 to 4. If the molar ratio of organic ligands to metal ions is lower than the above range, the porosity may be reduced. If the molar ratio of organic ligands to metal ions exceeds the above range, the size of the pores may be reduced.

[0093] Method for preparing porous carbon precursor

[0094] The present invention also provides a method for preparing a porous carbon precursor, the method comprising the following steps: (S1) heating a mixed solution obtained by dissolving a metal precursor and a first organic ligand precursor in an organic solvent to form a MOF; (S2) adding a second organic ligand containing at least one of N and S to the mixed solution and heating to form a MOF having a core-shell structure; and (S3) carbonizing the MOF having a core-shell structure formed in step (S2).

[0095] Hereinafter, the method for preparing a porous carbon precursor according to the present invention will be described in more detail with respect to each step.

[0096] In the present invention, in step (S1), MOF can be formed by heating a mixed solution obtained by dissolving a metal precursor and a first organic ligand precursor in an organic solvent.

[0097] The reaction conditions for forming the MOF are heating at a temperature of 100 to 150°C for 6 to 40 hours.

[0098] If the reaction temperature is lower than 100° C., it is difficult to initiate a crystal formation reaction, and thus MOF may not be formed. If the reaction temperature exceeds 150° C., MOF may not be formed.

[0099] In addition, if the reaction time is less than 6 hours, the reaction is terminated in a state where an intermediate product is formed, or the reaction is terminated in a mixed state of MOF and the intermediate product. If the reaction time exceeds 40 hours, the time required for the process may be too long, thereby reducing the process efficiency.

[0100] The metal precursor may be a compound containing the above-mentioned metal ions. For example, the metal precursor may include a zinc precursor, and the zinc precursor may include at least one selected from the following: zinc nitrate hexahydrate (Zn(NO3)2·6H2O), zinc acetate dihydrate (Zn(CH3CO2)2·2H2O) and zinc sulfate hexahydrate (ZnSO4·6H2O).

[0101] In addition, the first organic ligand precursor may include at least one selected from the following: benzene-1,4-dicarboxylic acid, benzene-1,3,5-tricarboxylic acid, 2-methylimidazole, oxalic acid, malonic acid, succinic acid, glutaric acid, phthalic acid, isophthalic acid, terephthalic acid, 2-hydroxy-1,2,3-propanetricarboxylic acid, 1H-1,2,3-triazole, 1H-1,2,4-triazole and 3,4-dihydroxy-3-cyclobutene-1,2-dione, preferably 1,4-benzenedicarboxylic acid.

[0102] In addition, the organic solvent may include at least one selected from the following: dimethyl carbonate, dimethylformamide (DMF), N-methylformamide, sulfolane (tetrahydrothiophene-1,1-dioxide), 3-methylsulfolane, N-butyl sulfone, dimethyl sulfoxide, pyrrolidone (HEP), N-(2-hydroxyethyl)-2-pyrrolidone (HEP), dimethyl piperidone (DMPD), N-methylpyrrolidone (NMP), N-methylacetamide, dimethylacetamide (DMAc), N,N-dimethylformamide (DMF), diethylacetamide (DEAc), dipropylacetamide (DPAc), ethanol, propanol, butanol, hexanol, ethylene glycol, tetrachloroethylene, propylene glycol, toluene, tripentine, methyl acetate, ethyl acetate, petroleum ether, acetone, cresol and glycerol, preferably dimethylformamide (DMF).

[0103] In the present invention, in step (S2), a second organic ligand precursor containing at least one of N and S may be added to the mixed solution formed with MOF and heated to form a MOF having a core-shell structure. In this case, the second organic ligand may be used in the state of a solution dissolved in an organic solvent. The organic solvent may be the same as or different from the range of the type of the organic solvent used in step (S1).

[0104] The reaction conditions for synthesizing MOF having a core-shell structure are heating at 35° C. to 100° C. for 15 minutes to 25 hours. If the reaction temperature or time is less than such reaction temperature or time, the ligand exchange reaction rate is too slow. If the reaction temperature or time exceeds such reaction temperature or time, the crystallinity may be destroyed by heat.

[0105] The synthesized MOF can be supported in a second organic ligand precursor solution so as to be able to react. In this case, the synthesized MOF can be supported in a second organic ligand solution in a crystalline state after washing, activation and drying. In the second organic ligand precursor solution supporting the MOF, a solvent-assisted ligand exchange reaction occurs, so that the surface of the MOF is doped with at least one of N and S, which are heteroelements and are contained in the second organic ligand precursor.

[0106] In this case, the MOF interior not doped with heteroelement in the MOF can be referred to as the first MOF, and the surface portion doped with heteroelement can be classified as the second MOF. In addition, the first MOF is referred to as the core, and the second MOF is referred to as the shell, thereby being able to form a MOF having a core-shell structure.

[0107] Generally, a solvent-assisted ligand exchange reaction is a reaction in which a ligand solution exchanges the parent ligand and daughter ligand of a parent MOF and obtains a daughter MOF that retains the topological structure of the parent MOF. At this time, all parent MOFs are converted into daughter MOFs according to the control of reaction conditions (e.g., temperature, concentration, crystal size, etc.) and the characteristics of the daughter ligands, or they are sequentially converted from the surface of the parent MOF to form a core-shell structure. During the ligand exchange process, the ΔG associated with the linker exchange process converges to zero (0), which can be considered as equilibrium.

[0108] According to one embodiment of the present invention, the parent ligand is terephthalic acid and the daughter ligand is 2-aminoterephthalic acid, and during the exchange process, the parent MOF is not completely converted into the daughter MOF due to the steric hindrance of the amine group present in the 2-aminoterephthalic acid, thereby forming a core-shell structure.

[0109] Ligand exchange can be confirmed by a change in crystal color, a yellow boundary on OM, FT-IR, FIB-EDS, NMR, etc., and the conversion rate can be determined by NMR analysis.

[0110] Figure 1 is a schematic diagram illustrating a process of forming a MOF having a core-shell structure in a method of preparing a MOF according to the present invention.

[0111] refer to Figure 1, ① shows a schematic diagram of the MOF formed in step (S1). ② shows a schematic diagram of the initial MOF, wherein the surface of the MOF begins to be doped with N while the solvent-assisted ligand exchange reaction between the MOF and the second organic ligand precursor is started in step (S2). ③ is a schematic diagram of a core-shell structured MOF divided into a first MOF and a second MOF, wherein the solvent-assisted ligand exchange reaction is completed and the surface of the MOF is doped with heteroelements. At this time, the second MOF forming the shell is doped with heteroelements.

[0112] The second organic ligand precursor may contain one or more of N and S.

[0113] The second organic ligand precursor containing N may include at least one selected from the following: 2-aminoterephthalic acid, 4-aminophthalic acid, 4-aminoisophthalic acid, 5-aminoisophthalic acid, 2,5-diaminoterephthalic acid, 2,2'-diamino-4,4'-stilbene dicarboxylic acid, 5-cyano-1,3-benzenedicarboxylic acid, 2-methylimidazole and 4,4',4"-s-triazine-2,4,6-triyl-tribenzoic acid.

[0114] The second organic ligand precursor containing S may include at least one selected from the group consisting of 2,5-dimercaptoterephthalic acid (H4(C8H2O4S2)), 2-mercaptoterephthalic acid, and 2,5-thiophenedicarboxylic acid.

[0115] In the present invention, in step (S3), the core-shell structured MOF formed in step (S2) is heat-treated and carbonized to prepare a porous carbon precursor.

[0116] The heat treatment may be performed under an inert atmosphere. The inert atmosphere may be formed of nitrogen, argon, helium, krypton or xenon, preferably argon.

[0117] The heat treatment temperature may be 900° C. to 1500° C., specifically 900° C. or more, 950° C. or more, or 1000° C. or more and 1100° C. or less, 1300° C. or less, or 1500° C. or less. If the heat treatment temperature is lower than 900° C., the Zn metal in the MOF may not be sufficiently removed. If the heat treatment temperature exceeds 1500° C., the process efficiency may be reduced because the process requires a lot of time and energy.

[0118] The heat treatment time can be 6 hours to 24 hours, specifically more than 6 hours, more than 7 hours or more than 8 hours and less than 22 hours, less than 23 hours or less than 24 hours. If the heat treatment time is less than 6 hours, carbonization is insufficient, so that it may be difficult to ensure sufficient specific surface area and pore volume required for the electrochemical reaction. If the heat treatment time exceeds 24 hours, the process efficiency may be reduced because the process requires a lot of time and energy.

[0119] Lithium secondary battery

[0120] The present invention also relates to a lithium secondary battery, which comprises a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, wherein the porous carbon precursor as described above may be included as a positive electrode material.

[0121] Specifically, when a sulfur-containing material is used as a positive electrode active material, the porous carbon precursor can be used as a sulfur carrier. Thus, a battery containing a sulfur-containing material as a positive electrode active material can be called a lithium-sulfur secondary battery.

[0122] In the present invention, the positive electrode of the lithium secondary battery may include a positive electrode collector and a positive electrode mixture layer having a positive electrode active material formed on the positive electrode collector.

[0123] The positive electrode active material may include elemental sulfur (S8), sulfur compounds, or a mixture of the above materials. The sulfur compounds may specifically include Li2S n (n≥1), organic sulfur compounds or carbon-sulfur polymers (C2S x ) n : x=2.5 to 50, n≥2). In the case of these sulfur materials, since they do not have conductivity alone, they can also be used in the positive electrode of a lithium secondary battery in the form of a sulfur-carbon composite material formed by being composited with a carbon material.

[0124] In addition, the positive electrode active material may also include a lithium-containing transition metal oxide, which may be any one selected from the following or a mixture of two or more thereof: LiCoO2, LiNiO2, LiMnO2, LiMn2O4, Li(Ni a Co b Mn c )O2(0 <a<1,0<b<1,0<c<1,a+b+c=1)、LiNi 1-y Co y O2、LiCo 1-y Mn y O2、Li Ni 1-y Mn y O2(O≤y<1), Li(Ni a Co b Mn c )O4(0 <a<2,0<b<2,0<c<2,a+b+c=2)、LiMn 2-z Ni z O4、LiMn 2-z Co zO4(0 < z < 2), LiCoPO4, and LiFePO4. In addition to these oxides, sulfides, selenides, halides, etc. can also be used.

[0125] In addition, there is no particular limitation on the positive electrode current collector as long as it has high conductivity and does not cause chemical changes in the relevant battery. For example, stainless steel, aluminum, nickel, titanium, sintered carbon can be used; or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. In this case, the positive electrode current collector can be formed in various forms such as a film, sheet, foil, net, porous body, foam, or non-woven fabric having fine irregularities formed on its surface to enhance the bonding force with the positive electrode active material.

[0126] In the present invention, the negative electrode of the lithium secondary battery may include a negative electrode current collector and a negative electrode mixture layer having a negative electrode active material formed on the negative electrode current collector.

[0127] As the negative electrode active material, a carbon material, lithium metal, silicon, tin, etc. that can intercalate and deintercalate lithium ions can be used. Preferably, a carbon material can be used, and as the carbon material, low-crystalline carbon and high-crystalline carbon can be used. As the low-crystalline carbon, typically soft carbon and hard carbon. As the high-crystalline carbon, typically high-temperature sintered carbon such as natural graphite, condensated graphite, pyrolytic carbon, mesophase pitch-based carbon fiber, mesophase carbon microbead, mesophase pitch, and coke derived from petroleum or coal tar pitch. In this case, the negative electrode may include a binder. The binder can be various binder polymers such as vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, and polymethyl methacrylate.

[0128] In addition, there is no particular limitation on the negative electrode current collector as long as it has conductivity and does not cause chemical changes in the relevant battery. For example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon can be used; copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc.; or an aluminum-cadmium alloy. In addition, similar to the positive electrode current collector, the negative electrode current collector can be formed in various forms such as a film, sheet, foil, net, porous body, foam, or non-woven fabric having fine irregularities formed on its surface.

[0129] At this time, the positive electrode mixture layer or the negative electrode mixture layer may further include a binder resin, a conductive material, a filler, and other additives.

[0130] Binder resin is used for the combination of electrode active material and conductive material and the combination of current collector. Examples of such binder resins may include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene propylene diene monomer rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber, fluororubber and various copolymers of the above materials.

[0131] The conductive material is used to further improve the conductivity of the electrode active material. There is no particular limitation on the conductive material as long as it has conductivity and does not cause chemical changes in the relevant battery. For example, it is possible to use: graphite, such as natural graphite or artificial graphite; carbon black materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers and metal fibers; carbon fluoride; metal powders, such as aluminum powder and nickel powder; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; polyphenylene derivatives.

[0132] The filler is selectively used as a component for suppressing electrode expansion and is not particularly limited as long as it is a fibrous material and does not cause chemical changes in the relevant battery, and includes, for example: olefin polymers such as polyethylene and polypropylene; and fibrous materials such as glass fiber and carbon fiber.

[0133] In the present invention, the diaphragm is a physical diaphragm having the function of physically separating the electrode, and can be used without particular restriction, as long as it is used as a diaphragm in a conventional lithium secondary battery, in particular, preferably a diaphragm with low resistance to ion migration in the electrolyte and excellent impregnation capacity for the electrolyte. Specifically, a porous polymer film can be used alone or with its laminate, and the porous polymer film is, for example, a porous polymer film made of a polyolefin polymer (such as ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer, ethylene / methacrylate copolymer, etc.), or a conventional porous nonwoven fabric can be used, such as a nonwoven fabric made of high melting point glass fiber, polyethylene terephthalate fiber, etc., but is not limited thereto.

[0134] In the present invention, the electrolyte may be a non-aqueous electrolyte, and the electrolyte salt contained in the non-aqueous electrolyte is a lithium salt. The lithium salt may be used without limitation as long as it is commonly used in an electrolyte for a lithium secondary battery. For example, the lithium salt may be at least one selected from the following: LiFSI, LiPF6, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10, LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiPF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, lithium chloroborane and lithium tetraphenylborate.

[0135] As the organic solvent contained in the non-aqueous electrolyte, organic solvents commonly used in electrolytes for lithium secondary batteries can be used without limitation, for example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc. can be used alone or in combination of two or more thereof. Among them, carbonate compounds can be included, which are typically cyclic carbonates, linear carbonates, or combinations thereof.

[0136] Specific examples of cyclic carbonate compounds may be at least one selected from the following or a combination of two or more thereof: ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate and halides thereof. Examples of these halides include, but are not limited to, fluoroethylene carbonate (FEC) and the like.

[0137] In addition, the specific example of the straight-chain carbonate compound can be typically but not limited to at least one selected from the following or a combination of two or more thereof: dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate and ethyl propyl carbonate. In particular, ethylene carbonate and propylene carbonate as cyclic carbonates in carbonate organic solvents are high-viscosity organic solvents with high dielectric constants, so that the lithium salts in the electrolyte can be more easily dissociated. If this cyclic carbonate is mixed with a straight-chain carbonate (such as dimethyl carbonate and diethyl carbonate) with low viscosity and low dielectric constant in an appropriate ratio, an electrolyte with higher conductivity can be manufactured.

[0138] In addition, the ether in the organic solvent may be, but is not limited to, at least one selected from the following or a combination of two or more thereof: dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether and ethyl propyl ether.

[0139] In addition, the ester in the organic solvent can be but is not limited to at least one selected from the following or a combination of two or more thereof: methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone.

[0140] The nonaqueous electrolyte can be injected at an appropriate stage in the electrochemical device manufacturing process according to the manufacturing process and required properties of the final product. That is, the nonaqueous electrolyte can be injected before assembling the electrochemical device or at the final stage of assembling the electrochemical device.

[0141] In the case of the lithium secondary battery according to the present invention, in addition to the winding process as a general process, a process of laminating or stacking and folding a separator and an electrode may be performed.

[0142] In addition, there is no particular limitation on the shape of the battery case, and may be various shapes such as cylindrical, laminated, square, pouch, or coin. The structure and manufacturing method of these batteries are well known in the art, and thus a detailed description thereof will be omitted.

[0143] In addition, lithium secondary batteries may be classified into various batteries such as lithium-sulfur secondary batteries, lithium-air batteries, lithium-oxide batteries, and lithium all-solid-state batteries according to the positive / negative electrode materials used.

[0144] Furthermore, the present invention provides a battery module including the lithium secondary battery as a unit cell.

[0145] The battery module can be used as a power source for medium or large-sized devices requiring high temperature stability, long cycle characteristics, high capacity characteristics, and the like.

[0146] Examples of medium and large devices may include, but are not limited to: power tools powered and moved by electric motors; electric vehicles, including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles, including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0147] Preferred Implementation

[0148] Hereinafter, in order to help understand the present invention, preferred embodiments of the present invention will be described. However, it will be apparent to those skilled in the art that the following embodiments are used to illustrate the present invention, and various modifications and variations can be made within the scope and spirit of the present invention, and such modifications and variations are naturally within the scope of the appended claims.

[0149] Example 1

[0150] (1) Preparation of MOF

[0151] 0.8 g (4.2 mmol) of Zn(NO3)2·6H2O and 0.149 g (0.89 mmol) of 1,4-benzenedicarboxylic acid (H2BDC) were placed in a 50 mL container together with 30 mL of anhydrous DMF (N,N'-dimethylformamide). The reaction solution was heated at 120°C for 1 day in a box-type electric furnace. The crystalline product was obtained by a decompression device and filter paper, and washed several times with anhydrous DMF (N,N'-dimethylformamide) and anhydrous chloroform. The product was dried in a vacuum dryer at room temperature.

[0152] The prepared MOF is MOF-5 (Zn4O(BDC)3, BDC: 1,4-benzenedicarboxylate).

[0153] (2) Formation of core-shell structure (MOF-5@N-MOF-5)

[0154] 2-Aminoterephthalic acid as a N-containing organic ligand precursor was dissolved in DMF (N,N′-dimethylformamide) as an organic solvent to prepare an organic ligand precursor solution having a concentration of 0.01M.

[0155] After the organic ligand precursor solution was heated at 100° C. for 30 minutes, the resulting MOF having a core-shell structure (MOF-5@N-MOF-5) was recovered and dried.

[0156] (3) Carbonization

[0157] The MOF with a core-shell structure was heat-treated at 1000 °C for 6 h in an Ar atmosphere to prepare a porous carbon precursor (MOF-5@N-MOF-5).

[0158] Example 2

[0159] A porous carbon precursor (MOF-5@S-MOF-5) was prepared in the same manner as in Example 1, except that 2,5-mercaptoterephthalic acid as an organic ligand precursor containing element S was used instead of 2-aminoterephthalic acid as an organic ligand precursor containing element N.

[0160] Comparative Example 1

[0161] MOF-5 was carbonized in the same manner as in Example 1, except that the core-shell structure was not formed, to prepare porous carbon (MOF-5).

[0162] Comparative Example 2

[0163] N-MOF-5 was carbonized in the same manner as in Example 1, except that the core-shell structure was not formed, to prepare porous carbon (N-MOF-5).

[0164] Comparative Example 3

[0165] Porous carbon (N-MOF-5@MOF-5) was prepared in the same manner as in Example 1, except that the materials of the core and shell were reversed.

[0166] Experimental Example 1

[0167] The shapes of the porous carbon precursors prepared in Examples 1 and 2 and Comparative Example 1, respectively, were confirmed.

[0168] Figure 2 are scanning electron microscope (SEM) (FE-SEM; JEOL, JSM-7100F) photographs of MOFs prepared in Examples 1 and 2 and Comparative Example 1, respectively.

[0169] refer to Figure 2 It can be seen that the porous carbon precursors of Examples 1 and 2 and Comparative Example 1 are all cubic. In addition, in the case of Examples 1 and 2, it can be seen that another layer is further formed on the surface of the cubic shape, whereby it can be seen that a core-shell shape is formed.

[0170] Figure 3 : are graphs (2θ level) showing the results of XRD (X-ray diffraction) analysis of the porous carbon precursors prepared in Example 1 and Comparative Examples 1, 2 and 3, respectively.

[0171] refer to Figure 3 It can be seen that the main peaks (6.8°, 9.7°, 13.7°, 15.4°) of Comparative Example 1 (MOF-5) and Comparative Example 2 (N-MOF-5) are the same, and the main peaks of Example 1 (MOF-5@N-MOF-5) and Comparative Example 2 (N-MOF-5@MOF-5) are also the same, indicating that the crystal structure of the existing MOF is retained even after the ligand exchange reaction.

[0172] Figure 4 are optical microscope photographs of the porous carbon precursors prepared in Examples 1 and 2 and Comparative Examples 1, 2 and 3, respectively.

[0173] refer to Figure 4 It can be seen that Example 1 (MOF-5@N-MOF-5), Example 2 (MOF-5@S-MOF-5) and Comparative Example 3 (N-MOF-5@MOF-5) which are MOF forms with core-shell structures after the ligand exchange reaction retain the cubic shapes of Comparative Example 1 (MOF-5) and Comparative Example 2 (N-MOF-5) which are MOF forms with existing structures.

[0174] Figure 5 : is a graph showing the Fourier transform infrared spectroscopy (FT-IR) analysis results of MOF and its raw materials prepared in Example 1 and Comparative Example 1, respectively.

[0175] refer to Figure 5 It can be seen that the core-shell structure is formed by the amide group of 2-aminoterephthalic acid, which is the organic ligand precursor of N-MOF-5 (IRMOF-3) present in Example 1 (MOF-5@)N-MOF-5).

[0176] Experimental Example 2

[0177] Figure 6 The results of focused ion beam energy dispersive X-ray spectroscopy (FIB-EDS) measurement of the MOF prepared in Example 1 are shown.

[0178] refer to Figure 6 It can be seen that in the MOF of Example 1, the interior is separated from the surface, thereby forming a core-shell structure.

[0179] In addition, Table 1 below shows the elemental analysis results of the core surface and shell interior of the MOF of Example 1.

[0180] Table 1:

[0181] atom C N O Zn surface 68.10 3.08 17.41 11.41 internal 68.63 0 20.19 11.18

[0182] As shown in Table 1, it was confirmed that element N was detected only on the surface of MOF, that is, on the shell. This shows that the porous carbon precursor has a core-shell structure in which the core and the shell also have different constituent components.

[0183] Figure 7 The results of scanning electron microscope-energy dispersive X-ray spectrometer (SEM-EDS) (FE-SEM; JEOL, JSM-7100F) measurement of the MOF prepared in Example 2 are shown.

[0184] refer to Figure 7 , it can be confirmed that the porous carbon precursor of Example 2 has a core-shell structure in which a shell is formed on the surface of a cubic core. In addition, S is observed only in the shell, indicating that the composition of the core and the shell is different. It can be seen that a MOF having a core-shell structure is formed. The shell is observed in a fractured shape, and as the S element is distributed along the fractured portion, it can be seen that a shell made of a composition different from that of the core is formed.

[0185] Figure 8a and 8b Results of X-ray photoelectron spectroscopy (XPS) (Thermo UK, K-α) measurements of the porous carbon precursors prepared in Example 1 and Example 2 are shown, respectively.

[0186] refer to Figure 8a and Figure 8bIt can be seen that the binding energies of N and S as impurity elements can be confirmed, and thus it can be seen that they are well doped.

[0187] In addition, Table 2 below shows analysis results of components of the porous carbon precursors prepared in Examples 1 and 2 and Comparative Example 1, respectively.

[0188] Table 2:

[0189] C O N S Comparative Example 1 97 2.5 0.5 - Example 1 91.9 6.9 1.0 0.3 Example 2 95.4 1.8 0.7 2.1

[0190] As shown in Table 2, it can be confirmed that in Example 1 and Example 2, since 2-aminoterephthalic acid containing N and 2,5-dimercaptoterephthalic acid containing S were used as organic ligand precursors, respectively, the contents of N and S were also high in the component analysis results.

[0191] Experimental Example 3

[0192] Figures 9a to 9c : are graphs showing the BET analysis results of the porous carbon precursors prepared in Examples and Comparative Examples, respectively.

[0193] refer to Figures 9a to 9c It can be seen that in Examples 1 and 2, as heteroatoms are doped into the outer shell of the hierarchical porous carbon precursor, micropores develop, and then as the micropores develop, the specific surface area and pore volume of the porous carbon precursor increase compared to Comparative Example 1.

[0194] On the other hand, it can be seen that Comparative Example 3 in which the core and shell materials are formed inverted has significantly smaller pore volume and specific surface area than Comparative Example 1, compared with Comparative Example 2 and Example 1 which are not hierarchical porous carbon precursors.

[0195] The pore volumes and specific surface areas of the porous carbon precursors of Examples 1 and 2 and Comparative Examples 1 to 3 are shown in Table 3 below.

[0196] Table 3:

[0197]

[0198] Experimental Example 4

[0199] The electrochemical performance of lithium-sulfur secondary batteries according to the types of porous carbon precursors used as positive electrode materials were evaluated.

[0200] As a subject for electrochemical performance evaluation, a lithium-sulfur secondary battery was manufactured as follows.

[0201] The separator is placed between the positive electrode and the negative electrode, thereby placing it in the shell, and then the electrolyte is injected into the shell to prepare a lithium-sulfur secondary battery in the form of a CR-2032 coin cell. At this time, the positive electrode is prepared by coating the positive electrode slurry formed by mixing the positive electrode active material, the conductive material (Super P) and the binder (styrene-butadiene rubber, SBR) in a weight ratio of 80:10:10 on an Al foil, which is then dried and rolled. The positive electrode active material is a sulfur-carbon composite material (S loading: 70%) obtained by mixing sulfur (a product derived from Sigma-Aldrich) with a porous carbon precursor using a ball mill and then heat-treating it at 155°C.

[0202] As the negative electrode, lithium foil was used.

[0203] The electrolyte was obtained by dissolving 0.3 M LiNO 3 and 1 M LiTFSi in a mixed solvent of DOL and DME (DOL:DME=1:1 (volume / volume)) (DOL: dioxolane, DME: dimethoxyethane).

[0204] At this time, as the porous carbon precursor, the porous carbon precursors of Example 1 and Comparative Examples 1, 2 and 3 were used respectively.

[0205] Experimental Example 4-1

[0206] After the prepared lithium-sulfur secondary battery was charged and discharged under 0.1C conditions, the initial capacity and the discharge capacity at 14 cycles were measured, and the performance retention rate was calculated, and the results are shown in the following Tables 4 and Fig.10 middle.

[0207] Table 4

[0208]

[0209] The results showed that the electrochemical performance of the lithium-sulfur secondary battery containing the porous carbon precursor of Example 1 was the best, and it can be seen that this was due to the fact that the porous carbon precursor of Example 1 had a layered core-shell structure, in particular, micropores were developed in the shell and the shell was doped with heteroelements.

[0210] Experimental Example 4-2

[0211] After the prepared lithium-sulfur secondary batteries were charged and discharged at 0.1C, the capacities after 1 cycle and 30 cycles were compared.

[0212] Fig.11a and Fig.11b Graphs showing the capacities of batteries including Example 1 and Comparative Example 1 after 1 cycle and 30 cycles.

[0213] refer to Fig.11a and Fig.11b Example 1 (MOF-5@N-MOF-5) showed an improved initial discharge capacity (initial capacity, Example 1: 939.96 mAh·g) compared with Comparative Example 1 (MOF-5). -1 , Comparative Example 1: 810.66 mAh g -1 ).

[0214] In addition, in Example 1, the discharge capacity was higher even after 30 cycles, indicating improved performance retention (discharge capacity after 30 cycles, Example 1: 705.62 mAh·g -1 (75% performance retention), Comparative Example 1: 810.66 mAh g -1 (73% performance retention)).

[0215] It was confirmed that the degree of electrode polarization was lower in Example 1.

[0216] Experimental Example 5

[0217] The NMR peaks of the porous carbon precursors synthesized in Examples and Comparative Examples were confirmed.

[0218] The synthesized porous carbon precursor crystals were dissolved in 1 M sodium deuterated (NaOD) solution, and the NMR of the organic ligands was measured.

[0219] Fig.12a is a graph showing changes in the NMR peak of the porous carbon precursor of Example 1 according to the synthesis time, and Figure 12b It is a graph showing changes in NMR peaks of Example 1 and Comparative Examples 1, 2, and 3.

[0220] refer to Fig.12a , the H1 peak (*) in the BDC benzene ring of MOF-5 still remains in the porous carbon precursor (MOF-5@N-MOF-5) of Example 1, but is not found in N-MOF-5 using BDC-NH2 as the organic ligand.

[0221] It was also confirmed that in the case of MOF-5@N-MOF-5, as the ligand exchange reaction time increased, the H1 main peaks (A, B, C) of the BDC-NH2 organic ligands of MOF-5@N-MOF-5 were shown, and their sizes increased.

[0222] refer to Figure 12bIn the case of Example 1 (MOF-5@N-MOF-5) and Comparative Example 3 (N-MOF-5@MOF-5), both Comparative Example 1 (MOF-5) and Comparative Example 2 (N-MOF-5) showed main peaks (*, A, B, C), which means that ligand exchange occurred in the precursor MOF.

[0223] Experimental Example 6

[0224] By measuring the contact angles of the electrodes containing the porous carbon precursors in Example 1 and Comparative Example 1, the wettability of the electrodes to the electrolyte was determined.

[0225] Fig.13 3 is a photograph showing the measurement results of the contact angles of the negative electrodes (cathodes) including the porous carbon precursors of Example 1 and Comparative Example 1.

[0226] refer to Fig.13 It was found that the negative electrode containing MOF-5 as the porous carbon precursor of Comparative Example 1 was pure carbon having no heteroatoms and had hydrophobicity, and had a contact angle with water of 57.9°.

[0227] Furthermore, it was shown that the negative electrode including MOF-5@N-MOF-5 as the porous carbon precursor of Example 1 was N-doped carbon, had increased electronegativity and was hydrophilic, and had a water contact angle of 33.3°.

[0228] From the measurement results of the contact angle of water, the negative electrode containing MOF-5@N-MOF-5 of Example 1 has a lower contact angle and improved polarity, thereby improving the wettability of the electrolyte and improving the binding force with lithium ions, thereby improving the performance of the battery.

[0229] In the above content, although the present invention is described through limited embodiments and drawings, the present invention is not limited thereto, and it is obvious to those skilled in the art that various modifications and variations can be made within the scope equivalent to the technical spirit of the present invention and the appended claims.

Claims

1. A porous carbon material for a positive electrode for a lithium secondary battery, obtained by carbonizing a cubic porous carbon precursor having a core-shell structure, in, The core comprises a first MOF and the shell comprises a second MOF, wherein the core is not doped with heteroelement, The first MOF is MOF-5, and the second MOF is MOF-5 doped with an impurity element including at least one of N and S.

2. The porous carbon material according to claim 1, wherein The porous carbon material has a pore volume of 1.5 cc / g to 4.5 cc / g.

3. The porous carbon material according to claim 1, wherein The porous carbon material has 1500 m 2 / g to 3000m 2 / g specific surface area.

4. A method for preparing the porous carbon material according to claim 1, the method comprising the following steps: (S1) heating a mixed solution obtained by dissolving a metal precursor and a first organic ligand precursor in an organic solvent to form a MOF; (S2) adding a second organic ligand containing at least one of N and S to the mixed solution and heating to form a MOF having a core-shell structure; and (S3) Carbonizing the MOF having a core-shell structure formed in step (S2).

5. The method for preparing a porous carbon material according to claim 4, wherein: The metal precursor includes at least one selected from the group consisting of zinc nitrate·hexahydrate, zinc acetate·dihydrate and zinc sulfate·hexahydrate.

6. The method for preparing a porous carbon material according to claim 4, wherein: The first organic ligand precursor includes at least one selected from the group consisting of benzene-1,4-dicarboxylic acid, benzene-1,3,5-tricarboxylic acid, oxalic acid, malonic acid, succinic acid, glutaric acid, phthalic acid, isophthalic acid, terephthalic acid and 2-hydroxy-1,2,3-propanetricarboxylic acid.

7. The method for preparing a porous carbon material according to claim 4, wherein: The second organic ligand precursor in step (S2) is selected from a second organic ligand precursor containing N and a second organic ligand precursor containing S, The N-containing second organic ligand precursor comprises at least one selected from the following: 2-aminoterephthalic acid, 4-aminophthalic acid, 4-aminoisophthalic acid, 5-aminoisophthalic acid, 2,5-diaminoterephthalic acid, 2,2'-diamino-4,4'-stilbene dicarboxylic acid, 5-cyano-1,3-benzenedicarboxylic acid and 4,4',4"-s-triazine-2,4,6-triyl-tribenzoic acid, and The sulfur-containing second organic ligand precursor includes at least one selected from the following: 2,5-dimercaptoterephthalic acid, 2-mercaptoterephthalic acid and 2,5-thiophenedicarboxylic acid.

8. The method for preparing a porous carbon material according to claim 4, wherein: In step (S2), heating is performed at 35°C to 100°C for 15 minutes to 25 hours.

9. The method for preparing a porous carbon material according to claim 4, wherein: In step (S3), carbonization is performed at a temperature of 900°C to 1500°C under an inert atmosphere. 10 . A positive electrode for a lithium secondary battery, comprising the porous carbon material according to claim 1 .

11. The positive electrode for a lithium secondary battery according to claim 10, wherein The positive electrode comprises a positive electrode active material, The positive electrode active material comprises: a sulfur-containing material; and a porous carbon material as a sulfur carrier.

12. A lithium secondary battery, comprising: The positive electrode according to claim 10; negative electrode; a separator, the separator being interposed between the positive electrode and the negative electrode; and Electrolyte.

Citation Information

Patent Citations

  • A package vessel having curve type volume

    KR2020000021214U

  • Fabrication method and application of one-dimensional MOF@ZIF core-shell structure

    CN110212194A

  • KR20200021217A